A simple fluorescence turn-on chemosensor based on Schiff-base for Hg2+-selective detection. Issue 38 (21st September 2016) - Su, Qiuchen; Niu, Qingfen; Sun, Tao; Li, Tianduo
Graphical abstract: Highlights: A simple and low cost fluorescence turn-on chemosensorL for Hg 2+ was described. L showed a high selectivity and sensitivity and rapid reversibility toward Hg 2+ . The low detection limit for Hg 2+ was 2.268 × 10 –8  M. The recognition behavior can function well over a wide range of pH value. Abstract: A simple and effective Schiff-base fluorescent chemosensorL was synthesized, which showed highly selective and sensitive detection of Hg 2+ ions in CH3 CN/H2 O (9:1, v/v) solution over a wide pH range. SensorL exhibited a specific 'turn-on' fluorescent response to Hg 2+ with a low detection limit of 2.268 × 10 –8  M. The complex solution ofL with Hg 2+ ion exhibited reversibility with EDTA and regenerated free ligand for further Hg 2+ sensing. The results implied that sensorL could effectively act as Hg 2+ sensor in aqueous CH3 CN media.